VICTORIAN ERA IN GREAT EXPECTATIONS NOVEL BY CHARLES DICKENS (An Analysis of Wolfgang Iser’s Theory) - Nurul Wahidah; Anisa Nur’aini (Nusantara Hasana Journal, 2024)
This research explores the Victorian era in Great Expectations by Charles Dickens, using Iser’s theory The Act of Reading: A Theory of Aesthetic Response (1978). The theoretical framework of this study is the repertoire of the text. The research method is descriptive qualitative analysis. The main source of this study is the novel Great Expectations, published in 2002, which consists of 20 chapters and 484 pages. The research instrument is note-taking. Data collection techniques include reading, classification, and concluding. The data analysis method used is the reading method, the act of reading that conducted by the reader to produce the meaning. This study finds several significant achievements as a repertoire of the novel in the Victorian era, such as Revolution industry, wealth, social class, love, and gentlemanly ideals. These elements represent the repertoire of the text, captured in Great Expectations through the act of reading to evoke an aesthetic response.